Observations on How People in Two Locations of the Plateau Département of Southeast Benin Perceive Entomophagy: A Study From West Africa - Ghosh, Sampat; Tchibozo, Séverin; Lanmantchion, Euloge; Meyer-Rochow, Victor Benno; Jung, Chuleui (Frontiers in Nutrition, 2021)
Abstract：We surveyed the local populations of Kétou and Pobè in Southeast Benin through interviews and with the aid of a semi structured questionnaire in order to understand how they currently perceive entomophagy, an age old tradition in their communities. The study revealed that the majority of the population was familiar with the use of insects as food and a sizable number of people were still interested in insect consumption. Gender differences were not apparent. Tradition or culture was identified as the most influential factor, followed by taste, as determinants for eating or rejecting insects. However, identifying the edible species and comparing practices how they were prepared for consumption, we found that the knowledge was not homogenous across the society of Benin with differences depending on ethnicity, culture, respondent’s age, and educational background. Awareness and promotion of food insects in the society should help to preserve the practice of entomophagy and in turn could lead to the provision of much needed nutritional supplements to the poorer and disadvantaged sections of the society.